2022
DOI: 10.1001/jamapsychiatry.2022.2742
|View full text |Cite
|
Sign up to set email alerts
|

Penetrance and Pleiotropy of Polygenic Risk Scores for Schizophrenia, Bipolar Disorder, and Depression Among Adults in the US Veterans Affairs Health Care System

Abstract: for the Cooperative Studies Program (CSP) #572 and Million Veteran Program (MVP)IMPORTANCE Serious mental illnesses, including schizophrenia, bipolar disorder, and depression, are heritable, highly multifactorial disorders and major causes of disability worldwide.OBJECTIVE To benchmark the penetrance of current neuropsychiatric polygenic risk scores (PRSs) in the Veterans Health Administration health care system and to explore associations between PRS and broad categories of human disease via phenome-wide asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…First, we consider effective dilution between two separate GWA studies using the presence of one (1; lenient) or at least two (2+; strict) phecode counts for bipolar disorder in the Million Veteran Program (MVP), leveraging non-overlapping patients (and controls) for each analysis. As expected from our prior work 19 (Fig. 3, Tables S2, S3).…”
Section: Applications: Use Cases For Effective Dilutionsupporting
confidence: 89%
“…First, we consider effective dilution between two separate GWA studies using the presence of one (1; lenient) or at least two (2+; strict) phecode counts for bipolar disorder in the Million Veteran Program (MVP), leveraging non-overlapping patients (and controls) for each analysis. As expected from our prior work 19 (Fig. 3, Tables S2, S3).…”
Section: Applications: Use Cases For Effective Dilutionsupporting
confidence: 89%
“…A study of 106,160 patients not only showed a strong association with schizophrenia but also with anxiety, mood, substance use, personality disorders and suicidal behaviour (Zheutlin et al, 2019). Similarly, in a study in the United States Veterans Affairs Health Care System in patients with schizophrenia, bipolar disorder and depression, higher PRSs were associated with higher likelihood of mental and physical health diagnoses, although the effect size was lower in African ancestry individuals than in those of European ancestry (Bigdeli et al, 2022). A phenome-wide analysis of UK Biobank participants has shown that highly pleiotropic variants corresponded to ubiquitously expressed genes important for extracellular matrix, regulation of cell growth and signalling pathways (Shikov et al, 2020).…”
Section: Depressionmentioning
confidence: 98%
“…This hypothesis-free approach, referred to as a phenome-wide association study (PheWAS), can aid in understanding pleiotropic effects. Recent PheWASs using PGSs for other psychiatric problems (eg, schizophrenia, bipolar disorder, and depression) have identified widespread associations between PGSs and a host of psychiatric and other medical diagnoses …”
Section: Introductionmentioning
confidence: 99%